Optimization of ship's bow for the added resistance in waves - Bolbot, Victor (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ναυπηγών Μηχανολόγων Μηχανικών. Τομέας Μελέτης Πλοίου και Θαλασσίων Μεταφορών, 2016)
Every shipping company has a goal to reduce operational costs and increase income. One possible way to achieve that is by optimizing ship's hull in respect to calm water resistance. However, because ships seldom travel at still water conditions, it is important also to introduce the effect of the added resistance in waves. For large ships, added resistance in waves is mainly the result of wave diffraction around the ship while the added resistance due to motions has a small contribution. The available theoretical methods at the moment find it hard to evaluate accurately the diffraction component of added resistance in short waves. This makes necessary the use of semi-empirical approach or CFD methods. Added resistance is also important for minimization of the Energy Efficiency Design Index (EEDI). Added resistance affects the selection of suitable Sea Margin and fw correction factor, which accounts for the decrease of speed in representative sea conditions. A reduction in added resistance will affect positively the EEDI. The development of computers during last century allowed the use of parametric models created in CAD/CAE systems for representation of hulls forms. New optimization solution techniques such as Sobol functions and genetic algorithms set up the necessary background for effective and quick optimization. All of these are present in CAESES/Friendship-Framework. In this diploma thesis, the bow of a large tanker (KVLCC2) is optimized in terms of the added resistance in waves using CAESES/Friendship-Framework for creation of parametric model and optimization. Ship's bow is also optimized for total resistance, using Holtrop-Mennen method for estimation of calm water resistance. In the last stage, ship's bow is optimized for EEDI. The resulted maximum continuous rating of ship's main engine is compared with the minimum required power in adverse conditions.